Stratification and synthesis of crop–livestock production systems using GIS - Jagtap, S.S.; Amissah-Arthur, A.A. (1999)
Population increases, land-use changes and marketing opportunities are important factors affecting crop-livestock integra- tion particularly with respect to their effect on soil fertility and feed supply for ruminant livestock. As the human population density rises, crop farmers and grazers are finding it profitable to establish contracts for paddocking, and they are reaching agreement on equitable ways to make use of crop residues and take care of livestocks. As the processes of intensification proceed, mixed crop-livestock systems are evolving as the viable and dominant farming system, allowing smallholder farmers to capitalize on the complementarity between crops and livestock. Strategies directed to raise the productivity of specific crop-livestock systems need to consider the stage of development of the target area in relation to intensification and the nature of crop-livestock interactions. Information related to crop and livestock systems in West Africa is currently available from various sources e.g., household surveys, aerial surveys, rural appraisal, experimental etc., and held by different agencies. The approach used in this study shows how such data (biophysical and socioeconomic) can be integrated within a GIS environment and synthesized to identify the evolution of systems across environments and also to identify constraints and potential of the systems. Potential for integrated crop-livestock systems remains untapped and/or knowledge of its existence is unknown for large parts of Nigeria. Using data from 36 case studies and georeferenced data on cropping intensities and livestock population for the entire country, it was possible to predict emerging crop-livestock systems using GIS. Indeed, depending on availability of data, it is now possible to extend a similar approach in other African countries. The potential contribution of this technology is largely unknown in West and Central Africa, where few operational programs use them. Major technological innovations and appropriate government policies have potential to shift the balance in regional developments, if targeted carefully at areas where the right conditions exist. Further research could then target specific areas thus ensuring efficient allocation of resources while policy makers can achieve development goals by directing policies and resources to domains that have the greatest potential